CFD-моделювання температурного поля корпуса-радіатора передавального модуля АФАР з повітряним охолодженням - Nikolaenko, Yu.; Baranyuk, O.; Reva, S.; Rohachov, V. (PE "Politekhperiodika", Book and Journal Publishers, 2019)
Frequency multipliers are used in electronic devices to generate spectrally pure sinusoidal signals in the frequency range from a few to tens of GHz. The multipliers are used to multiply the frequency of highly stable but more low-frequency devices with the subsequent extraction of the necessary harmonics from the frequency spectrum of the received microwave range. The frequencies selected after multiplication (set) have significantly higher energy, spectral and range characteristics, which allows them to be used as local oscillators and synthesizers in receiving and transmitting systems.The authors of this paper theoretically substantiate and practically demonstrate the possibility of an unconventional implementation of a microstrip multiplier of the microwave range based on a directional traveling wave filter. The proposed implementation does not require the use of active semiconductor elements.The well-known circuit and technological principles for the creation of microstrip microwave multipliers are considered in the paper. The features, problems and shortcomings arising from their implementation are analyzed. The effectiveness of using the balanced circuit for frequency multiplication is confirmed. A list of mandatory requirements and conditions necessary for the implementation of the microwave multipliers is given. It is demonstrated that the features of the microstrip travelling-wave filter are identical to the conditions and requirements for the implementation of balanced multipliers. It is shown and substantiated how an unconventional implementation of a passive microwave multiplier is possible due to the electromagnetic interaction of the input and output nodes of such a filter with an annular travelling-wave resonator. Using the example of modifying a block diagram of a directional filter into a multiplier circuit, the possibility of creating a microwave doubler is confirmed by separating a given frequency from the frequency spectrum of a traveling-wave ring resonator.